Selection of the Amino Acid and Saccharide That Increase the Tetracycline Susceptibility of Vibrio splendidus - Jiang, Guohua; Li, Yanan; Li, Ya; Zhang, Weiwei; Li, Chenghua (Frontiers in Veterinary Science, 2022)
Bacterial persister cells are a subpopulation of isogenic bacteria with characteristics of reduced metabolic activity and multidrug antibiotic resistance. Our lab had previously proved that Vibrio splendidus could form persister cells both naturally and after stimulation (1). However, the conditions for the wake up of V. splendidus persister cells remain margin. In this study, the carbon sources that could wake up V. splendidus persister cells were selected from 20 amino acids and eight saccharides. The result showed that L-glutamic acid, L-aspartic acid, L-arginine, L-phenylalanine, L-leucine, maltose, D-galactose, sorbitol, mannose, N-acety-D-glucosamine, D-glucose and D-fructose could wake up the V. splendidus persister cells. The chemotaxis activity of both exponential cells and regrown persister cells on plate containing each of the selected carbon source are also high. The exist of the selected carbon source can affect the antibiotic susceptibility of V. splendidus. When L-glutamic acid, L-aspartic acid, L-phenylalanine and D-glucose were separately added into the cultured V. splendidus simultaneously with tetracycline, V. splendidus could be completely eliminated, while the addition of L-alanine and D-galactose could not. Our study suggested that V. splendidus persister cells could revive in the presence of specific carbon sources, and the addition of these exogenous nutrients could increase the tetracycline susceptibility of V. splendidus.